Minors using Ritalin: obstacles in Primary Health Care surveillance - Maycon Hoffmann Cheffer; Bianca Machado Cruz Shibukawa; Gabriele da Silva Borges; Elisete Teleginski Dietrichkeit; Terezinha Aparecida Campos; Maria Aparecida Salci; Ieda Harumi Higarashi (Universidade Federal do Ceará, 2022)
Objective: to understand how nursing workers from Family Health Strategy teams track children and adolescents using Ritalin. Methods: qualitative study, based on the theoretical references of the essential primary health care attributes. The participants were 27 nurses from the Family Health Strategy. Data collection took place through interviews later submitted to content analysis in the NVivo software. Results: three categories emerged: (Lack of) knowledge about the population who uses Ritalin: co-responsibilities in the process of assistance and difficulties to follow up on the use of Ritalin; Primary care knowledge and know-how in the setting of Ritalin use; The prescription of Ritalin as a demand from schools. Conclusion: the monitoring of children and adolescents who use Ritalin has shortcomings, and primary health care must organize itself to increase and strengthen the care to this population.